The impact of leadership on the psychosocial safety climate of organizations: A scoping review of the international literature - Laloo, Eugene; Coman, Robyn; Hanley, Natalia; Bakand, Shahnaz (International Journal of Occupational Safety and Health, 2023)
Growing evidence suggests that work-related psychological injuries are a concern worldwide. While previous efforts to address psychological injuries mainly focused on the individual level of analysis, psychosocial safety climate (PSC) theory emphasizes the analysis and prevention of psychological injuries at the organizational level. While there is abundant evidence of the impact of leadership on other climate constructs, scant attention has been paid to the impact of leadership on PSC. This study is a scoping review of the extant literature to determine the state of the discipline in relation to the impact of leadership on the psychosocial safety climate of organizations. Three databases were searched, supplemented by a pearling exercise and Google Scholar searches, which yielded 14 studies that met selection criteria. Our study shows that while much work has been done in relation to the behavior of managers and organizational infrastructure to yield high levels of PSC, there is a dearth of studies on the impact of specific leadership styles on the PSC of organizations. We recommend further studies of leadership, especially the impact of post-heroic leadership styles, on the psychosocial safety climate of workplaces.